Psychological Capital and University Students’ Entrepreneurial Intention in China: Mediation Effect of Entrepreneurial Capitals - Zhao, Jianbo; Wei, Guojiang; Chen, Kou-Hsiung; Yien, Jui-Mei (Frontiers in Psychology, 2020)
The aim of this study was to identify the influences of psychological capital on students’ entrepreneurial intention in China’s Universities. The mediating effects of Entrepreneurial Capitals were also examined. Based on the analysis of the traditional capital and psychological capital, the paper proposes that traditional capital is the direct factor to drive the behavior of entrepreneurship, while psychological factors do not directly affect entrepreneurial intention, but improve entrepreneurial intention by influencing traditional capital. A total of 1914 responses from universities in southeast China were analyzed using the structural equation modeling (SEM) approach to test study hypotheses. Results show that psychological capital has a significant indirect impact on students’ entrepreneurial intention only through traditional financial, human and social capital. These results support the mediating role of the traditional entrepreneurial capitals in explaining the relationship between psychological capital and entrepreneurial intention. Additionally, the impact of social capital on entrepreneurial intention is higher than that of financial and human capital. Finally, Research limitations and implications are discussed and future research directions are suggested.